The Pledge of Allegiance - Chang, Kirsten, 1991- (Blastoff! readers. Symbols of American freedom., 2019)
"Developed by literacy experts for students in kindergarten through grade three, this book introduces the Pledge of Allegiance to young readers through leveled text and related photos"--